Measurement Of Speakeraes Power Response And Impluse Response - Liman, Johansah; Madra, Quinta Nadya (Teknik dan Ilmu Komputer, 2017)
One way to find out the acoustic performance of a room is by measuring the impulse response. These measurements will obtainÃÂ an overview of interaction between the sound source and the surface in the room, which can be described in a time sequence patterns of sound energy reflection at any point in the room as well as the reduction of sound energy at any time or any sound reflections information. This research aims to determine the amount of power response and impulse response of sounds produced by speakers. Variable in this research is sounds produced through a microphone and that go out through the speaker. To determine the power response, pink noise is measured, while the impulse response is measured using impulse signals. SPL meter is used to measure the power response and impulse response. The research is literature study and field observation. The result shows the impulse response measurement is not easily interrupted by frequencies from other sound sources. Meanwhile, power response is easily distracted by the frequency from other sound sources.ÃÂ Keywords: impulse signal, impulse response, pink noise, power response, SPL meter